2004
DOI: 10.1002/qua.20386
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of structure of catalytic copper site in nitrite reductase

Abstract: ABSTRACT:The catalytic copper site in nitrite reductase contains a Cu 2ϩ ion bound to three histidine (His) ligands and a solvent molecule. Sites from various sources show a conspicuous variation in the structure. In some proteins, it is close to tetrahedral (even more so than are blue copper proteins), whereas in other proteins, it has a structure more similar to that expected for a type 2 copper site. We have studied this site with a number of theoretical methods, ranging from vacuum optimizations, combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 56 publications
(77 reference statements)
4
42
0
Order By: Relevance
“…This finding is in accordance with theoretical studies on the pH dependence of Cu-NiRs (39). An explicit coupling between structure and activity is emphasized through additional studies showing the reduced nitrite affinity at high pH, by changes in the reduction potential of the type 2 copper ion with pH, and by the presence or absence of protons on the solvent ligands and neighboring residues of the type 2 copper ion.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in accordance with theoretical studies on the pH dependence of Cu-NiRs (39). An explicit coupling between structure and activity is emphasized through additional studies showing the reduced nitrite affinity at high pH, by changes in the reduction potential of the type 2 copper ion with pH, and by the presence or absence of protons on the solvent ligands and neighboring residues of the type 2 copper ion.…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, it is not physically consistent, but only motivated by the frequent observation that QM/MM methods with electrostatic embedding seem to overestimate electrostatic interactions. 41,49 The ME' method itself, as well as the physically more consistent ME av method, also give better results than QM-only, but with slightly worse MUEs and MSEs than ME scal .…”
Section: Discussionmentioning
confidence: 97%
“…The rationale for this is that it has frequently been observed that electrostatic interaction energies are overestimated by QM/MM. 26,41,42 A problem with all of the previous ME methods is that they are sensitive to the stability of the ESP charges used for the QM system. In particular, for a large QM system, any variation of the charges on the boundary of the QM system will make large contributions to the energy difference between various states, because they are close to the MM system.…”
Section: Mechanical Embeddingmentioning
confidence: 99%
“…[15][16][17] In the following study, the properties of different states of a model CuNiR active site have been investigated through quantum chemical methods, including several possible enzyme mechanism pathways and the geometry of substrate-binding.…”
Section: Introductionmentioning
confidence: 99%